ONLINE LEARNING SYSTEM ACCEPTANCE BY INDONESIAN HIGH SCHOOL STUDENTS DURING THE COVID-19 PANDEMIC WITH UTAUT - Nofitriyani Nofitriyani; Fathul Wahid; Ahmad R Pratama (Jurnal Teknik Informatika (Jutif), 2022)
The Covid-19 outbreak that spread rapidly around the world including in Indonesia, has affected various fields, one of which is education. The government’s policy concerning PSBB forced the schools to change th learning process into online learning. However, there are factors to consider in its application, one of which is student acceptance of the learning method. This study was conducted with the participation of 437 Indonesian high school students in Indonesia. The analysis was conducted using the Structural Equation Modeling (SEM) method, with the Unified Theory of Acceptance and Use of Technology (UTAUT) acceptance model serving as the theoretical framework and being supplemented by three new exogenous variables. The findings suggest that the additional variable Perceived Enjoyment is the most influential factor on the acceptance of online learning systems among Indonesian high school students during the COVID-19 pandemic. In addition, of the four original exogenous variables in UTAUT, only Effort Expectancy and Facilitating Condition play a significant role in increasing students' intention to continue adopting online learning systems. The findings from this study can serve as a guide for secondary school online learning policies, even after the pandemic has ended.